Horizontal together : art, dance, and queer embodiment in 1960s New York - Aramphongphan, Paisid (Manchester : Manchester University Press, 2021)
Horizontal together is an up-close look at the cultural and political power of the langourous queer body, combining historical research, queer theory and the analysis of bodily gestures. The book presents a dancerly story of 1960s art focusing on Andy Warhol, underground filmmaker Jack Smith and experimental dance star Fred Herko.
Front matter -- Contents -- List of plates -- List of figures -- Acknowledgements -- Introduction -- 1 The moves that queer bodies make -- 2 The queer horizontal repertoire -- 3 Plastiques -- Plates -- 4 Dancing queers -- 5 Repetition and queer difference -- Coda -- Bibliography -- Index
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on May 19, 2021).
JSTOR
Keywords: Herko, Fred; Smith, Jack, -- 1932-1989.; Warhol, Andy, -- 1928-1987.; Herko, Fred; Smith, Jack, -- 1932-1989.; Warhol, Andy, -- 1928-1987.; Warhol, Andy, -- 1928-1987; Smith, Jack, -- 1932-1989; Herko, Fred; Homosexuality and the arts -- New York (State) -- New York -- History -- 20th century; Homosexualité et arts -- New York (État) -- New York -- Histoire -- 20e siècle.; ART / Performance; Homosexuality and the arts; New York (State) -- New York; 1900-1999; Arts; Art; History